ANALISIS KELAYAKAN USAHA PENGGEMUKAN DOMBA PADA KELOMPOK TERNAK MULYO JAYA DESA DOYOMULYO KECAMATAN KEMBANGBAHU KABUPATEN LAMONGAN - Wijaya, Hengky Saputra; Anela Kurniasari, Dwiyana (Jurnal Agribisnis Wijaya Putra Surabaya, 2024)
This research was conducted in the sheep fattening business in the Mulyo Jaya livestock group, Doyomulyo Village, Kembangbahu District, Lamongan Regency. This study aims to determine the feasibility of sheep fattening business and determine the scale of sheep ownership that must be raised to obtain income equivalent to the Lamongan City Minimum Wage (UMK). This research was carried out for 3 months, namely in February 2023 - April 2023. The type of research used was quantitative. The sample used in this study is a saturated sample. The types of data used in this study are qualitative data and quantitative data. Sources of data used in this study are primary data and secondary data. Data collection was carried out by means of observation, questionnaires and interviews. The results of this study indicate that the business of fattening sheep in the Mulyo Jaya livestock group is feasible and if it refers to the UMK of Lamongan City in 2023 it is Rp. 2,701,977, then the sheep fattening business with a scale of 50 heads earns an income of Rp. 3,335,827 which means it is higher than the city's UMK.